PENCEGAHAN KLITIH MELALUI PENDEKATAN BUDAYA BACA PADA SISWA DI DAERAH ISTIMEWA YOGYAKARTA - Sukirno Sukirno (Ikatan Pustakawan Indonesia, 2018)
Klitih is a violence that be done by teenager in Daerah Istimewa Yogyakarta. The player is teenager and as a student in a school. Klitih is not just a teenage naughtiness but a crime, so that it makes mass anxious. Klitih becomes a challenge for DIY government in realizing vision of 2030 to be a student and tourism city. This research is purposed to: (1) giving solution to prevent students from klitih by reading culture approach, (2) building character by reading culture to students of DIY. The method of the research is by Case Study. Collecting data by observation with the hope to get information about Klitih. Based on research, it is gotten data that in 2016 there were 43 cases , with dead-victim more than one. The effort to prevent Klitih involves many parties, either local government, school, parents and police. One of the ways to prevent Klitih is by reading culture approach to students . Reading culture can be used to make students character. Student character is signed by rising of responsibility of moral-value and obeying the norm. Futhermore, the research can be done to get more complete data so that Klitih will be able to be handled better.